Pengaruh Keterampilan Mengajar Guru terhadap Hasil Belajar Siswa Sekolah Dasar - Amel Fitriani; Nabella Yaniariza Putri Pratama; Salsha Fairuz Putri Isa; Septi Yunita (Journal on Education, 2022)
This study aims to examine the effect of teacher teaching skills on student learning outcomes in elementary schools. In this study, it will specifically examine teaching skills and learning readiness as factors that can influence student learning outcomes. The teacher's teaching skills are very important in the learning process because one of the ways the teacher can do it is so that the learning process in the classroom fosters effective student learning activities and learning outcomes can be as expected. Learning activities are not enough just to listen and take notes, but must be more complex than that. This shows that the teacher's teaching skills must be able to make students able to stimulate various learning activities. In preparing this article, we used a qualitative approach with literature studies based on several scientific journals, electronic books, and other sources whose accuracy has been confirmed. The results of this study describe that there is an influence of teacher teaching skills on student learning outcomes in elementary schools. By mastering the basic skills of teaching, the teacher can train all learning materials so as to achieve the learning objectives themselves